Language and Brain: Neurological Aspects in Language Acquisition - Rizki Amalia Sholihah (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2022)
The human nervous system consists of two parts, namely the spine and the brain. The brain itself consists of the brain stem and cerebral cortex, consisting of the right and left hemispheres. Each hemisphere is divided into four lobes: the frontal lobe, occipital lobe, temporal lobe, and parietal lobe, where each lobe has its function—the brain experiences both growth regarding its parts and mass or weight. The left and right hemispheres have their respective roles or functions, leading to a tendency to use hemispheres. The left hemisphere is more dominantly responsible for language, logical and analytical matters. At the same time, the right hemisphere is more intuitive and imaginative. Concerning producing speech, the brain has a part called the Broca region. Then there is the Wernicke area which is responsible for speech comprehension. These two regions will work together for language processing in the brain. Besides, there is a system related to the workings of emotions in humans called the limbic system in the brain.